Case Report: First Documented Hip Arthroplasty on Chinese Patient with Ochronotic Arthropathy - Ying, Zhibo; Lu, Jufeng; Wang, Xucheng; Zeng, Qinghe; Jin, Hongting; He, Bangjian (Frontiers in Surgery, 2022)
Alkaptonuria (AKU) is a rare autosomal recessive disorder caused by homogentisc acid (HGA) accumulation, the deposition of which in the joints usually causes ochronotic arthropathy. With no specific therapy for AKU currently, total joint arthroplasty in ochronotic arthropathy is applied to relieve the symptoms. A 63-year-old female patient came to our Orthopedic Surgery Department in 2019, complaining of severe limitation of movement and pain in the right hip for more than one year. A right total hip arthroplasy (THA) was performed due to the ineffective conservative therapy. At a follow-up of more than 15 months, the woman had full mobility with no complaining of pains. Since there is no relevant case reported about THA therapy for Chinese AKU patients, this report provides a feasible scheme, which makes clinical data more comprehensive.